KURIKULUM KULLIYATU AL-MU’ALLIMIN AL-ISLAMIYYAH (KMI) UNTUK MENINGKATKAN SUMBER DAYA MANUSIA DALAM ERA GLOBALISASI DI PONDOK MODERN SIROJUL MUNIR - Dzul Azmi, Muhammad; Victorynie, Irnie (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
Pondok Modern Sirojul Munir implements the Kulliyatu Al-Mu’allimin Al-Islamiyyah (KMI) curriculum as a strategy to improve the quality of human resources (HR) in addressing the challenges of the globalization era. This curriculum focuses on mastering Arabic and English languages and developing Islamic character. This study aims to identify the key factors driving the adoption of the KMI curriculum, examine the challenges encountered during its implementation, and analyze strategies to overcome these obstacles. The research employs a qualitative approach, utilizing interviews, observations, and document analysis as data collection methods. The findings reveal that the KMI curriculum significantly contributes to enhancing the quality of students’ HR, despite challenges such as adaptation issues, limited language proficiency, and low public awareness. Pondok Modern Sirojul Munir employs various strategies, including counseling programs, facility upgrades, and intensive monitoring, to address these challenges. This study provides insights into the potential of the KMI curriculum as a pesantren education model that aligns with contemporary demands.